HUBUNGAN USIA, INFEKSI, RIWAYAT PENYAKIT, PARITAS DENGAN KEJADIAN ABORTUS PADA IBU HAMIL DI RSUD CIKALONGWETAN TAHUN 2024 - Tambunan, Yetti Natalia; Barbara, Maria Awaldina Dua (SINERGI : Jurnal Riset Ilmiah, 2025)
Background: Abortion is one of the most common reproductive health problems that occurs during the first trimester of pregnancy and contributes to high rates of maternal morbidity and mortality. Objective: This study aimed to determine the relationship between age, history of infection, medical history, and parity with the incidence of abortion among first-trimester pregnant women at Cikalongwetan Regional General Hospital in 2025. Methods: This research employed an analytic survey with a case-control design. The sample consisted of 88 respondents selected through purposive sampling from a total population of 389 pregnant women recorded in the 2024 medical records. Data were obtained from medical record documentation and analyzed using the Chi-Square test. Results: The univariate analysis showed that 50% of respondents experienced abortion, the majority were aged 20–35 years (70.5%), had a history of infection (44.3%), had a medical history (42.0%), and were multiparous (47.7%). Bivariate analysis revealed significant associations between age and abortion incidence (p=0.001), history of infection and abortion (p=0.003), medical history and abortion (p=0.001), as well as parity and abortion (p=0.03). The highest proportion of abortion cases was found among women aged >35 years (34.1%), those with a history of infection (59.1%), those with a medical history (25.0%), and those with grand multiparity (22.7%). Conclusion: Factors of age, infection history, medical history, and parity were significantly associated with the incidence of abortion among first-trimester pregnant women at Cikalongwetan Regional General Hospital. The findings are expected to serve as a reference for healthcare providers in conducting early detection and preventive interventions, as well as providing education to pregnant women regarding the importance of maintaining reproductive health and planning pregnancies at an ideal reproductive age